Dynamic Optimization in Supply Chains - Pupavac, Drago; Pašagić Škrinjar, Jasmin; Zelenika, Ratko (Promet - Traffic&Transportation, 2007)
Production and stock optimization in supply chains representsextremely complex problem, because it determines the optimumquantity production in time. Due to their multilevelednature, those problems are mostly solved by application of differentmethods and models of dynamic programming. Theproblem addressed in this scientific debate refers to determinationof optimum quantity of production and stocks within thesupply chain in a certain period of time, as well as in eachsub-interval of the said period, but with the condition that theproduction and stock expenditure remains minimal and thatthe predetermined demand in every sub-interval and throughoutthe entire observation period remains satisfied.